Trust measurement: comparative analysis of experimental and sociological methods = Mierzenie poziomu zaufania: analizy porównawcze metod eksperymentalnych i socjologicznych - Merkulova, Tamara; Bitkova, Tatiana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
There are 2 ways of trust measuring - experimental (using laboratory or field experiment) and sociological one (survey). Both are widely used by researchers all over the world. Therefore, comparison of experimental and sociological results is a hot topic, considered in many scientific works. In Ukraine laboratory experiments are not yet widespread in studying of trust, and mostly sociological methods are used.
Keywords: zaufanie; eksperyment laboratoryjny; sondaż; gry PG (Public Good); trust; laboratory experiment; sociological survey; PG game